Impact of Microphytobenthos Photosynthesis on the Characteristics of the Echo Signal from Baltic Sandy Sediments - Natalia GORSKA; Ewa KOWALSKA-DUDA; Jacek MARSZAL; Jan Henryk SCHMIDT; Zygmunt KLUSEK (Archives of Acoustics, 2015)
The understanding the influence of biological processes on the characteristics of the signals backscattered by the sea floor is crucial in the development of the hydroacoustical benthic habitat classification techniques. The impact of the microphytobenthos photosynthesis on the acoustical backscattering properties of the Atlantic sandy sediments was previously demonstrated by Holliday et al. (2004) and Wildman and Huettel (2012).